Anatomical study on the anterolateral ligament of the knee() - Helito, Camilo Partezani (Rev Bras Ortop, 2013)
OBJECTIVE: Describe the knee anterolateral ligament (ALL) and establish its anatomical marks of origin and insertion. METHODS: Dissection of the anterolateral aspect of the knee was performed in six cadavers. After isolation of the ALL, its lenght, width and thickness were measured as its places of origin and insertion. The ALL origin was documented in relation to the lateral collateral ligament (LCL) origin and the insertion was documented in relation to the Gerdy tubercle, fibullar head and lateral meniscus. After the first two dissections, the ligament was removed and sent to histologycal analysis. RESULTS: The ALL was clearly identified in all knees. Its origin in the lateral epycondile was on average 0.5 mm distal and 2.5 mm anterior to the LCL. In the tibia, two insertions were observed, one in the lateral meniscus and another in the proximal tibia, about 4.5 mm distal to the articular cartilage, between the Gerdy tubercle and the fibullar head. The average measures obtained were: 35.1 mm lenght, 6.8 mm width and 2.6 mm thickness. In the ligament histological analysis, dense connective tissue was observed. CONCLUSION: The ALL is a constant structure in the knee anterolateral region. Its origin is anterior and distal to the LCL origin. In the tibia, it has two insertions, one in the lateral meniscus and another in the proximal tibia between the Gerdy tubercle and the fibullar head.